2016
DOI: 10.1111/aor.12695
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Renal Failure and Renal Replacement Therapy on Outcome During Extracorporeal Membrane Oxygenation Therapy

Abstract: Acute kidney injury (AKI) is common in patients treated with veno-arterial (VA-) or veno-venous (VV-) extracorporeal membrane oxygenation (ECMO). In this setting, the use of continuous renal replacement therapy (CRRT) can help to optimize fluid status but may also negatively impact on patients' outcome. In contrast, the relationship between AKI, CRRT, and survival in critically ill adult patients receiving ECMO is not well defined. The institutional ECMO database (n = 162) from November 2008 to December 2013, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(78 citation statements)
references
References 40 publications
3
74
1
Order By: Relevance
“…AKI occurs very frequently in patients undergoing VA-ECMO. The prevalence in our study was about 92% while the prevalence of AKI in ICU patients has been estimated between 25 and 50% and between 70 and 85% in patients who underwent ECMO [12][13][14][15][16]. Comparing our findings with the latter results is challenging since the classification used, the population involved and the type of ECMO support were different.…”
Section: Discussioncontrasting
confidence: 67%
“…AKI occurs very frequently in patients undergoing VA-ECMO. The prevalence in our study was about 92% while the prevalence of AKI in ICU patients has been estimated between 25 and 50% and between 70 and 85% in patients who underwent ECMO [12][13][14][15][16]. Comparing our findings with the latter results is challenging since the classification used, the population involved and the type of ECMO support were different.…”
Section: Discussioncontrasting
confidence: 67%
“…Previous studies in patients treated with VA and VV ECMO demonstrated that the incidence of AKI exceeded 70% of whom around 50% needed RRT [54,55] . RRT can be provided by introducing the filter into the ECMO circuit (integrated system) or through separate venous access independent of the ECMO circuit (parallel system).…”
Section: Ecls In Respiratory Failurementioning
confidence: 98%
“…In 4 small, single-center studies looking at adult patients with AKI requiring combined therapy, the mortality rates were 60,78, 80, and 100%, respectively [5,7,10,11]. In a larger, more recent single-center study; 63 among 135 patients required combined ECMO and CRRT; however, mortality rates were similar among groups receiving ECMO without AKI, ECMO with AKI, and ECMO with AKI requiring CRRT [12].…”
Section: Introductionmentioning
confidence: 98%